NO CLOUD WITHOUT SKY: SPECTRUM SOVEREIGNTY AND ETHEREAL REFUSAL - Gagnon, Jeff (AoIR Selected Papers of Internet Research, 2021)
This paper will present the theoretical frameworks, research questions, and preliminary findings from 2 , a new study of movements for spectrum sovereignty. This foundational overview is a preliminary step toward a multi-year, international survey and case-study based project that aims to convene a space for the advancement of decolonized internet and communications networks predicated on the production of relational knowledges and the promotion of international solidarities. Centering the materiality of cyberspace necessarily reveals the relationships between the internet and settler colonialism. Such an acknowledgement is foundational to a decolonialist ethical point of view from which I argue for an understanding of space as relational practice, as resource, and as source of identity. A genuinely decolonized cyberspace that promotes the independence of colonized peoples is one that is subject to Indigenous spatial practices including territorial claims and treaty rights and so is one that is recognized as existing within space in a material way.